Perkembangan Tahap Individual Anak Usia Sekolah Dasar dalam Memahami Nilai-Nilai Agama - Siti Marwah; Khairunnisa Khairunnisa; Halimah Halimah; Hidayati Ramadhani; Surawan Surawan (JURNAL ILMU PENDIDIKAN, 2026)
The development of children at the elementary school age is a continuous and systematic process of change that includes physical, cognitive, socio-emotional, and religious aspects, with the age range of 6–12 years being a crucial stage in shaping values, attitudes, and spiritual identity. This study aims to examine the stages of individual development of elementary school children in understanding religious values using a qualitative approach with a literature study method by reviewing various relevant sources such as books and journals. The collected data are analyzed descriptively to illustrate child development and its implications for religious values education, and the findings show that children’s religious development is influenced by internal factors, as well as family and school environments; therefore, the roles of parents and teachers are essential in instilling religious values from an early age through habituation, role modeling, and guidance